Atom transfer between precision nanoclusters and polydispersed nanoparticles: a facile route for monodisperse alloy nanoparticles and their superstructures. Issue 43 (29th October 2020) - Bose, Paulami; Chakraborty, Papri; Mohanty, Jyoti Sarita; Nonappa,; Ray Chowdhuri, Angshuman; Khatun, Esma; Ahuja, Tripti; Mahendranath, Ananthu; Pradeep, Thalappil
Abstract : A unique method to prepare well-defined highly monodisperse gold–silver alloy nanoparticles through a chemical reaction of gold nanoclusters and polydispersed silver nanoparticles. Abstract : Reactions between atomically precise noble metal nanoclusters (NCs) have been studied widely in the recent past, but such processes between NCs and plasmonic nanoparticles (NPs) have not been explored earlier. For the first time, we demonstrate spontaneous reactions between an atomically precise NC, Au25 (PET)18 (PET = 2-phenylethanethiol), and polydispersed silver NPs with an average diameter of 4 nm and protected with PET, resulting in alloy NPs under ambient conditions. These reactions were specific to the nature of the protecting ligands as no reaction was observed between the Au25 (SBB)18 NC (SBB = 4-( tert -butyl)benzyl mercaptan) and the very same silver NPs. The mechanism involves an interparticle exchange of the metal and ligand species where the metal–ligand interface plays a vital role in controlling the reaction. The reaction proceeds through transient Au25− x Ag x (PET) n alloy cluster intermediates as observed in time-dependent electrospray ionization mass spectrometry (ESI MS). High-resolution transmission electron microscopy (HRTEM) analysis of the resulting dispersion showed the transformation of polydispersed silver NPs into highly monodisperse gold–silver alloy NPs which assembled to form 2-dimensional superlattices. Using NPs of other average sizes (3 and 8 nm), we demonstrated that size plays an important role in the reactivity as observed in ESI MS and HRTEM.